2012
DOI: 10.1088/1748-0221/7/10/p10010
|View full text |Cite
|
Sign up to set email alerts
|

High current proton source based on ECR discharge sustained by 37.5 GHz gyrotron radiation

Abstract: Formation of hydrogen ion beams with high intensity and low transverse emittance is one of the key challenges in accelerator technology. Present work is devoted to experimental investigation of proton beam production from dense plasma (Ne > 10 13 cm −3 ) of an ECR discharge sustained by 37.5 GHz, 100 kW gyrotron radiation at SMIS 37 facility at IAP RAS. The anticipated advantages of the SMIS 37 gasdynamic ion source over the current state-of-the-art proton source technology based on 2.45 GHz hydrogen discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 20 publications
2
25
0
Order By: Relevance
“…Experiments aimed to demonstrate the benefits of the high current gasdynamic ECR ion source as a part of D-D neutron generator were conducted at SMIS 37 facility [2], schematically depicted in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments aimed to demonstrate the benefits of the high current gasdynamic ECR ion source as a part of D-D neutron generator were conducted at SMIS 37 facility [2], schematically depicted in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of the extracted charge state distribution have shown that 94% of it consists of atomic deuterons (D+) (contribution of molecular D 2 + ions is less than 6%). For our knowledge such combination of parameters makes the obtained beam the brightest for any kind of ion sources with normalized rms brightness value of 100 A/( pi·mm·mrad) 2 .…”
Section: Fig 1 Smis 37 Experimental Facilitymentioning
confidence: 97%
“…The experimental results described in [4,5] demonstrate the feasibility of high power millimeter wave quasigasdynamic ECR ion sources for the production of high brightness proton beams with favorable species fraction. For the next experimental step on H+ and D+ ion beams production SMIS 37 facility was upgraded up to SMIS 75 by replacing of the old gyrotron with the new one with 75 GHz radiation frequency and 200 kW peak power.…”
Section: Introductionmentioning
confidence: 85%
“…Due to this coincidence, it was decided to test the gasdynamic ECR source performance for proton and deuteron beams formation. In previous papers, 15,16 it was demonstrated that proton beams with current of hundreds of mA could be produced. The latest results are presented below.…”
Section: Proton and Deuteron Beams Formationmentioning
confidence: 99%